BANK STOCK RESILIENCE TEST: THE IMPACT OF BITCOIN AND GOLD RISK CONTAGION IN THE TRUMP ERA - David Gabriel Marudut Purba; M. Ridho Akbar Lubis; Didik Gunawan; Willy Cahyadi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the dynamic relationship between gold price returns, Bitcoin returns, Bank Central Asia (BBCA) stock returns, and Bank Syariah Indonesia (BRIS) stock returns in the period before and after January 2025 as a representation of changes in global policy regimes in the Trump 2.0 era. The study uses a quantitative approach with the Vector Autoregression (VAR) method based on daily return data analyzed through stationarity tests, determining the optimum lag, VAR stability tests, cointegration tests, Granger causality tests, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD) using EViews 12. The results show that all variables are stationary at the level level so that the VAR model is suitable for use. Before January 2025, there was no significant Granger causality relationship between gold returns or Bitcoin returns on BBCA and BRIS stock returns. After January 2025, the dynamic relationship between variables changes, marked by the emergence of a causal relationship from BRIS returns to BBCA returns, while the direct relationship between gold returns and Bitcoin returns to banking stocks remains relatively limited. These findings suggest that changes in global policy regimes are more reflected in changes in the dynamics of relationships between assets than through direct risk transmission from gold and Bitcoin to Indonesian banking stocks.